The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1096/fj.14-254953
|View full text |Cite
|
Sign up to set email alerts
|

Development of an MRI biomarker sensitive to tetrameric visual arrestin 1 and its reduction via light‐evoked translocation in vivo

Abstract: Rod tetrameric arrestin 1 (tet-ARR1), stored in the outer nuclear layer/inner segments in the dark, modulates photoreceptor synaptic activity; light exposure stimulates a reduction via translocation to the outer segments for terminating G-protein coupled phototransduction signaling. Here, we test the hypothesis that intraretinal spin-lattice relaxation rate in the rotating frame (1/T1r), an endogenous MRI contrast mechanism, has high potential for evaluating rod tet-ARR1 and its reduction via translocation. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
(107 reference statements)
3
10
0
Order By: Relevance
“…Thus, at the present resolution, we previously demonstrated that MRI can distinguish rod inner segment from outer segment based on the light-evoked expansion of the subretinal space in mice and rats, as well as, for example, (1) inner from outer retina manganese uptake as a function of light, (2) DIL-induced suppression of only inner retinal manganese uptake, and (3) the outer nuclear layer-only tetrameric visual arrestin 1 and its reduction via light-evoked translocation. 28,29,50,51 These examples strongly support our claim that the resolution of MRI is sufficient for extracting meaningful layer-specific functional data in vivo. In all cases, animals were humanely euthanized as detailed in our IACUCapproved protocol.…”
Section: Mri Proceduressupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, at the present resolution, we previously demonstrated that MRI can distinguish rod inner segment from outer segment based on the light-evoked expansion of the subretinal space in mice and rats, as well as, for example, (1) inner from outer retina manganese uptake as a function of light, (2) DIL-induced suppression of only inner retinal manganese uptake, and (3) the outer nuclear layer-only tetrameric visual arrestin 1 and its reduction via light-evoked translocation. 28,29,50,51 These examples strongly support our claim that the resolution of MRI is sufficient for extracting meaningful layer-specific functional data in vivo. In all cases, animals were humanely euthanized as detailed in our IACUCapproved protocol.…”
Section: Mri Proceduressupporting
confidence: 69%
“…14,[23][24][25][26][27] However, subsequent studies have not found any evidence for a visual cycle defect in diabetic mice. 28 Thus, the mechanism by which 11-cis-retinaldehyde exerts its beneficial action in the diabetic mouse retina is still unclear.…”
mentioning
confidence: 99%
“…Retinyl esters participate in 11-cis-retinal formation (49) and are shown herein to accumulate to supranormal levels in diabetic retina, suggesting an impairment of retinoid dynamics in diabetic mice. However, other investigators (58) have not found evidence of abnormal visual cycle activity in diabetes. Maintenance of the visual cycle requires support from numerous mitochondria in photoreceptor cells, and our previous evidence (17,37) suggests that much of the superoxide generated by the retina in diabetes is generated by such mitochondria.…”
Section: Abca4mentioning
confidence: 91%
“…Thus, MRI evaluates the same set of rod cells for compartment-specific function in vivo using different types of acquisitions (see below for details; summarized in Fig. 4) (Berkowitz et al, , 2015a(Berkowitz et al, , 2015cBissig and Berkowitz, 2012). In addition, four "free" metrics are also obtained: retinal and choroidal thickness, and light-dependent expansion of the inner retinal circulation and choroid (Fig.…”
Section: Breakthroughmentioning
confidence: 99%
“…Thus, two additional MRI indices of rod cell functione measured without administration of exogenous contrast agents e have been developed to complement MEMRI and to facilitate translation of MRI of retinal function into humans. These methods are i) apparent diffusion coefficient (ADC) MRI, which measures light-evoked expansion of both SRS [controlled in part by the photoreceptors and in part by the retinal pigment epithelium (RPE)] and of the choroid (Berkowitz et al, 2015a;Bissig and Berkowitz, 2012), and ii) measurement of the spin-lattice relaxation rate in the rotating-frame (1/T1r) which evaluates lightstimulated rod arrestin and its translocation, together with retinal vessel expansion (Berkowitz et al, 2015c). As summarized in Fig.…”
Section: Non-memri Assays Of Rod Cell Functionmentioning
confidence: 99%